An integrated bioinformatics analysis to identify the shared biomarkers in patients with obstructive sleep apnea syndrome and nonalcoholic fatty liver disease - Zhang, Rou; Liu, Zhijuan; Li, Ran; Wang, Xiaona; Ai, Li; Li, Yongxia (Frontiers in Genetics, 2024)
Background: Obstructive sleep apnea syndrome (OSA) and nonalcoholic fatty liver disease (NAFLD) have been shown to have a close relationship in previous studies, but their pathogeneses are unclear. This study explores the molecular mechanisms associated with the pathogenesis of OSA and NAFLD and identifies key predictive genes.Using the Gene Expression Omnibus (GEO) database, we obtained gene expression profiles GSE38792 for OSA and GSE89632 for NAFLD and related clinical characteristics, respectively. Mitochondrial unfolded protein response-related genes (UPRmtRGs) were acquired by collating and collecting UPRmtRGs from the GeneCards database and relevant literature PubMed.The differentially expressed genes (DEGs) associated with OSA and NAFLD were identified using differential expression analysis. Gene Set Enrichment Analysis (GSEA)for signaling pathway enrichment analysis of related disease genes. Based on the STRING database, protein-protein interaction (PPI) analysis was performed on differentially co-expressed genes (Co-DEGs), and the Cytoscape software (version 3.9.1) was used to visualize the PPI network model. Besides, the GeneMANIA website is used to predict and construct the functional similar genes of the selected Co-DEGs.Key predictor genes are analyzed using the receiver operating characteristic curve (ROC).The intersection of differentially expressed genes shared between OSA and NAFLD-related gene expression profiles with UPRmtRGs yielded four Co-DEGs: ASS1, HDAC2, SIRT3, and VEGFA.GSEA obtained the relevant enrichment signaling pathways for OSA and NAFLD, respectively. PPI network results showed that all four Co-DEGs interacted (except for ASS1 and HDAC2). Ultimately, key predictor genes were selected in the ROC, including HDAC2 (OSA:AUC=0.812,NAFLD:AUC=0.729), SIRT3 (OSA:AUC=0.775,NAFLD:AUC=0.750), and VEGFA (OSA:AUC=0.812,NAFLD:AUC=0.861) (They have a high degree of accuracy in predicting whether a subject will develop two diseases).In this study, four co-expression differential genes for OSA and NAFLD were obtained, they can predict the occurrence of both diseases. Transcriptional mechanisms involved in OSA and NAFLD interactions may be better understood by exploring these key genes. Simultaneously, this study provides potential diagnostic and therapeutic markers for patients with OSA and NAFLD.